Neurosteroids Reduce Social Isolation-Induced Behavioral Deficits: A Proposed Link with Neurosteroid-Mediated Upregulation of BDNF Expression - Nin, Mauricio S.; Martinez, Luis; Pibiri, Fabio; Nelson, Marianela; Pinna, Graziano (Frontiers in Endocrinology, 2011)
The pharmacological action of selective serotonin reuptake inhibitor antidepressants may include a normalization of the decreased brain levels of the brain-derived neurotrophic factor (BDNF) and of neurosteroids such as the progesterone metabolite allopregnanolone, which are decreased in patients with depression and posttraumatic stress disorders (PTSD). The allopregnanolone and BDNF level decrease in PTSD and depressed patients is associated with behavioral symptom severity. Antidepressant treatment upregulates both allopregnanolone levels and the expression of BDNF in a manner that significantly correlates with improved symptomatology, which suggests that neurosteroid biosynthesis and BDNF expression may be interrelated. Preclinical studies using the socially isolated mouse as an animal model of behavioral deficits, which resemble some of the symptoms observed in PTSD patients, have shown that fluoxetine and derivatives improve anxiety-like behavior, fear responses and aggressive behavior by elevating the corticolimbic levels of allopregnanolone and BDNF mRNA expression. These actions appeared to be independent and more selective than the action of these drugs on serotonin reuptake inhibition. Hence, this review addresses the hypothesis that in PTSD or depressed patients, brain allopregnanolone levels, and BDNF expression upregulation may be mechanisms at least partially involved in the beneficial actions of antidepressants or other selective brain steroidogenic stimulant molecules.